Factors affecting hospital readmission in heart failure patients with reduced ejection fraction, Phrae Hospital - Lokkhamlue, Muthita (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
Heart failure with reduced ejection fraction is a cause of increased mortality and hospital readmission in many hospitals. Therefore, diagnosing the causes of recurrent heart failure is crucial so that patients receive correct and appropriate treatment. This research aimed to study the prevalence and factors affecting hospital readmission in heart failure patients with reduced ejection fraction at Phrae Hospital. This was an analytical, retrospective cohort study conducted in patients with heart failure with a left ventricular ejection fraction (LVEF) below 40% who received follow-up care at the Heart Center of Phrae Hospital for at least 6 months, from January 1, 2023 to December 31, 2023. The research instruments were data recording forms for patient medical records and information related to their heart failure condition. Data were presented as percentages, means and standard deviations. Factors affecting hospital readmission in heart failure patients with reduced ejection fraction were analyzed using Risk-ratio regression with a significance level set at p < 0.05. A total of 293 patients with heart failure with reduced ejection fraction who received follow-up care at the Heart Center, Phrae Hospital were included. The hospital readmission rate was 30.40%. It was found that hypertension, alcohol consumption, uncontrolled blood sugar levels, and incorrect medication use significantly affected hospital readmission (p = 0.00, p = 0.00, p < 0.00 and p < 0.00, respectively). Gender, other comorbidities, smoking, substance abuse, medications received, and treatments received (such as surgery, percutaneous coronary intervention with balloon angioplasty, etc.) were found to have no significant effect on hospital readmission.